2019
DOI: 10.1111/jcpe.13110
|View full text |Cite
|
Sign up to set email alerts
|

Infrabony defects 20 years after open flap debridement and guided tissue regeneration

Abstract: Aim Evaluation of 20‐year results after open flap debridement (OFD) and guided tissue regeneration (GTR) of infrabony defects in a randomized controlled trial. Materials and methods In originally 16 periodontitis patients (baseline examination), periodontal surgery was performed in 44 infrabony defects. Polylactide acetyltributyl citrate barriers were randomly assigned to 23 out of these 44 defects (parallel). Ten of these patients (GTR) exhibited a second, contra‐lateral defect (OFD) each (split‐mouth). At ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 34 publications
4
37
1
Order By: Relevance
“…In this study, 52.9% of the initially heavily diseased teeth were still in situ at the follow‐up examination up to 26 years after GTR therapy. This stands in marked contrast to Cortellini et al who described that all teeth that had received GTR therapy were still in function after 20 years (Cortellini et al., 2017) and to Petsos et al who reported a 20‐year tooth survival of about 79% in the sites treated with GTR (Petsos et al., 2019). This difference may be attributed to several factors: as outlined above, only about half of the defects included here received SPT with at least two regular recall appointments per year over the whole study period.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In this study, 52.9% of the initially heavily diseased teeth were still in situ at the follow‐up examination up to 26 years after GTR therapy. This stands in marked contrast to Cortellini et al who described that all teeth that had received GTR therapy were still in function after 20 years (Cortellini et al., 2017) and to Petsos et al who reported a 20‐year tooth survival of about 79% in the sites treated with GTR (Petsos et al., 2019). This difference may be attributed to several factors: as outlined above, only about half of the defects included here received SPT with at least two regular recall appointments per year over the whole study period.…”
Section: Discussionmentioning
confidence: 59%
“…Petsos et al. (2019) recently reported a mean CAL loss of 0.53 mm only between their 1‐year and their 20‐year examination. Likewise, Cortellini et al found mean new CAL losses of 0.1 mm or 0.5 mm between 1 and 20 years, depending on the surgical technique used (modified papilla preservation technique or access flap, respectively).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Guided bone regeneration (GBR) [7] is commonly used to treat conditions that reduce alveolar bone defects in the jaw [8][9][10].…”
Section: Introductionmentioning
confidence: 99%